Position of Eigendom Verponding after the Birth of the Basic Agrarian Law (Case Study of Dago Elos Supreme Court Decision Number 109PK/PDT/2022) - Gandawati, Dyah Ayu (TABELLIUS: Journal of Law, 2024)
Eigendom verponding is a product of land law from the Dutch East Indies era which is no longer valid after the birth of the national land law in 1960. Eigendom owners are required to carry out the conversion no later than September 24, 1980. However, the Supreme Court created its own law which is contrary to the spirit of agrarian reform. This type of research is a normative research that is prescriptive in nature. The data source in this study is secondary data obtained through literature studies. The results of the study show that the position of eigendom verponding is recognized as one of the land rights born from Dutch East Indies law and must be converted no later than September 24, 1980. Then the Government Regulation of 1997 and amended in 2021, conversion can still be carried out as long as it has been proven that there is physical control over the land by the former holder of the western land rights. The problem of converting eigendom verponding into ownership rights can be seen in the case of Heri Hermawan Muller et al. and PT. Dago Intigraha vs. Didi E. Koswara et al., and the Head of the Bandung City Land Office. The eigendom verponding land was not physically controlled by the former land rights holder, even though houses, post offices, and bus terminals had been built on the land. However, the Supreme Court decided that the land rights were still given to the holder of the western land rights.